How to make you spend more in the airport? An investigation towards ECSI model on willingness to spend more in airport - Shih, Ween Yong; Cheah, Jun-Hwa; Lim, Xin-Jean; Siew, Imm Ng; Yee, Choy Leong (Elsevier, 2023)
This study intends to uncover the potential drivers that motivate air passengers to spend more in the airport. To address the gaps in the literature, this study proposed a model that integrated the European Customer Satisfaction Index (ECSI) and Experience Economy Theory. Data was collected from 341 passengers at Kuala Lumpur International Airport and analyzed using Partial Least Squares - Structural Equation Modelling (PLS-SEM). The structural model results suggested that willingness to spend more depended on the passengers’ satisfaction and perceived value. Experience economy was found to mediate the path between airport image and passenger expectation on perceived value. Implications and suggestions for further research were discussed.